'Burned‐Out' primary testicular tumour: Is retroperitoneal lymph node biopsy mandatory prior to initiation of chemotherapy? Report of three cases and a review of the literature. (21st October 2021) - Vukovic, Marko; Kavaric, Petar; Vukmirovic, Filip; Lekic, Sanja
Abstract: The term 'burned‐out' tumour of the testis describes a spontaneously and completely regressed testicular tumour that presents at the stage of metastasis. We report three cases of burned‐out testicular tumour to illustrate their clinical, radiological and histopathological features and to discuss the hypothesis of the efficacy of early adjuvant chemotherapy without a previous retroperitoneal lymph node biopsy. Subsequent to radical orchiectomy, each pathohistology report revealed testicular hypotrophy or microcalcifications, with no clearly visible germ cell tumours within the specimen. Additionally, following surgery, the patients received the standard (cisplatin–etoposide–bleomycin) chemotherapy protocol, which in two out of three cases showed a complete response. Only one examinee revealed a partial response and received salvage chemotherapy, but he remained in the remission phase during the last follow‐up. This study illustrates the value of the early administration of adjuvant chemotherapy in patients with burned‐out testicular tumour, which offers the possibility of omitting the diagnostic retroperitoneal lymph node biopsy. Considering the low threshold for testicular malignancy, it is clearly of the utmost importance that these rare patients be treated in a timely manner and without adjunctive procedures (lymph node biopsy) leading to additional morbidity.